PERAN NILAI TUKAR PETANI DAN NILAI TUKAR KOMODITAS DALAM UPAYA PENINGKATAN KESEJAHTERAAN PETANI KEDELAI (Studi Kasus: Propinsi Jawa Timur) - ELIZABETH, ROOSGANDHA; DARWIS, VALERIANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Based on the main objective of agricultural development in this case, which are to increase the prospering of farmers and peasants life, its role are in: 1)setting and built in the “PDB”; 2)increasing the state income; 3)providing the job opportunities, especially for farmers and peasants. The objectives of this research were to: (a) describe soy-bean agribusiness performance; (b) analyze soy-bean’s term of trade; (c)influencing factors on terms of trade; (d) identifying the agricultural development impact on farmers terms of trade and soy-bean terms of trade. The result of this study among other things: 1) the cost for purchasing inputs was smaller compared to that labor’s terms of trade; 2) the R/C ratio of soy-bean farming development showed beneficial in large scale; 3) adopted soy-bean farming technology, production input and productivity level were such of internal factors; 4) market system was such of external, influence for farmer’s bargaining position. Therefore in order to meet that objective and to fulfill those rules, in formulation of many policies, the terms of trade and soy-bean terms of trade is used to be one of main considerations.
Keywords: Terms of Trade, Soybean, Prosperity of Farmer